The other side of the coin: do the benefits of being a Christian postgraduate at a secular university in England contribute to student wellbeing? - Watson, Szilvi (Journal of beliefs and values, 2026)
The mental-health crisis in higher education affects postgraduate students around the world, anxiety, depression and non-belonging being significant issues in this population. The positive relationships between faith and mental health and wellbeing are widely researched, yet little connection has been made between student mental health and religiosity. Half of postgraduate students in the UK identify with a religion or spirituality – exploring the benefits of faith on student mental health is vital. In this mixed methods case study, analysing 75 online survey responses and 17 interviews with and about Christian postgraduates at a red-brick university in England found that being a student of faith is a mixed experience. On the one hand, Christian students face various challenges on a secular campus, which may negatively affect their mental health and belonging, such as stereotyping, feeling counter-cultural and invisibility. Yet, personal faith and Christian communities provide a number of benefits to students, who reported that having faith significantly supports their mental health, gives them meaning and purpose and their belonging is facilitated by ready-made communities (e.g. churches). These advantages directly benefit both the students and their university, through providing pastoral and mental health support and potentially contributing to student retention. Postgraduate students struggle with their mental health at a higher rate than the general population, battling depression, anxiety and non-belonging. In addition, religious postgraduate students face difficulties which arise from their religious identity in a secular environment. However, the results of the present study suggest that Christian students benefit from their faith and faith communities, which support their mental health and aid their belonging. These factors improve their student experience and may contribute to student retention on postgraduate courses.